Professional Counselor Profile Analysis Based on Expert and User Expectations - Muhammad, Asrori (Advances in Social Sciences Research Journal, 2023)
The ultimate goal of the present research is to develop profiles and characteristics of professional counselors and their educational attainment as expected by experts and users so that standards for counselor education programs can be developed to produce professional counselor candidates. The specific objectives are (1) to describe the profile of a professional counselor having personal, social, and professional characteristics based on the expectations of experts and users; (2) to classify the sources of acquiring the profiles and characteristics expected by experts and users; and (3) to develop the standards for counselor education program.